Hepatobiliary and Gastrointestinal Involvement in Langerhans Cell Histiocytosis—Spectrum of Three Cases - Pratap, Thara; Jalal, Muhammed Jasim Abdul; R., Rashmi; Gopalakrishnabhakthan, Anupama; AK, Vishnu (Indian Journal of Radiology and Imaging, 2021)
Langerhans cell histiocytosis (LCH) is a rare group of disorder, due to clonal neoplastic proliferation of dendritic cells in the bone marrow expressing a Langerhans cell phenotype.1 This disease particularly affects the pediatric age group and young adults and often presents with skin rashes, lung infiltrates, and bone lesions. It can also manifest with endocrine dysfunction and hematopoietic disorders. Involvement of gastrointestinal tract is very rare. Herein, we present a spectrum of three cases with gastrointestinal involvement.
Keywords: histiocytosis; Langerhans cell; nodular; gastrointestinal; alanine aminotransferase